Moral internalisation influences the attentional bias to smoking and non-smoking stimuli in Malaysian youth - Shaharum MH,; Nasir Yusoff,; Reza F,; Ismail R,; Kueh, YC; Azman A, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The youth age group is a phase of life associated with risk-taking behaviour and challenging moral issues. This study aimed to provide electrophysiological evidence that could explain the interaction between attentional bias towards the health-risk of smoking and non-health risk behaviour stimuli as influenced by various levels of moral identity. Seventy eight eligible subjects (mean age of 22 + 2.1 years old) participated in the event-related potential session. Attentional bias towards the visual stimuli was determined by recording the N200 brain potential while participants emotionally reacted to the target (health-risk of smoking, nonhealth risk behaviour) and non-target (neutral) stimuli. N200 was extracted and analysed by using a mixed-design analysis of variance with target and non-target stimuli as within subject effects and types of moral identity as between subject effects. Attentional bias towards visual stimuli interacted significantly with the different levels of moral identity in the central part of the brain. High internalisation trait indicated shorter N200 latency when reacted to the health-risk of smoking stimuli than the non-health risk behaviour stimuli. An important insight regarding to moral psychology in relation to youth health risk behaviour was highlighted to focus for the development of the health promotion and education in future.